Minimally invasive stabilization of midshaft clavicle fractures using TENS: Impact on functional recovery and early mobilization - Sanikop, S. T.; Jain, Sarthak; Bhuti, Gangadhar (International Journal of Research in Orthopaedics, 2026)
Background: Clavicle fractures are commonly seen in young population, notably in those who are more active in sports, on the contrary, in elderly and children they are attributed mostly to falls, accounting for around 2.6% of all the fractures. The most common site of fracture in the clavicle occurs at the middle third and which accounts for almost 80% of all clavicle fractures. To explain the faster pain relief, early return of function and restitution of clavicle length with the help of reduction and internal fixation of clavicle fracture creating an elastic stability at the fracture gap. Methods: 32 patients presenting with mid shaft clavicle fractures in department of orthopaedics, KLEs Dr. Prabhakar Kore Hospital & Medical Research Centre and Charitable Hospital, were included in this study after taking their consent and fracture was stabilized using TENS nail. Results: In this study, it was noted that males were predominantly involved, maximum incidence between 20-30 years. Most of the cases had RTA as a mode of injury with right clavicle fracture predominance. Post operatively, patients were followed up and Oxford Shoulder Score (OSS) was calculated at 4, 8, 16 weeks and the improvement in OSS score was found to be statistically significant. Conclusions: We concluded that intramedullary fixation of displaced mid shaft clavicle fractures is a safe minimally invasive technique and is recommended in view of faster union, lesser morbidity, earlier rehabilitation and fewer complications.